Energy-Efficient Dehydration Regimes for Agricultural Products with the Application of Suspension Heat Treatment - Popescu V.S.; Tsislinscaia N.I.; Melenchiuc M.G.; Balan T.V.; Vishanu I.V.; Gydei I.P. (Problems of the Regional Energetics)
The aim of this study is to determine the energy-efficient dehydration regimes for agricultural products based on suspension heat treatment method. In order to achieve this goal, an electrical plant was designed, developed, tested, optimized and implemented, on the basis of which the research was carried out, applying in the drying process, namely the process of technological processing in suspension with the contribution of convection. The research was focused on the example of drying different agricultural products; in particular, the following products were selected as the main object of the research: hawthorn, apple, quince, pear and grape seeds. These agricultural products were selected as at the moment they were not fully exploited. Because of their rich content of vegetable oils with specific properties, they are of great interest to the food industry, traditional medicine, cosmetology, pharmacology, etc., and their drying using conventional methods is difficult, particularly because of defects and adverse reactions, which frequently occur in the technological processing. The main results obtained using the designed installation, are: reduction of the electricity consumption and the processing time, increase in the productivity and quality of the final products. The significance of the results obtained in the research lies in solving a number of problems currently faced by the processors, in connection with the improvement of equipment and increasing the efficiency of the drying process, mainly by increasing the energy efficiency, processing speed, quality of products and profitability.